Role of Family Milieu in Tobacco Addiction: A Study in a Tertiary-care Institution in India (Journal of Health, Population and Nutrition, 2013)
Use of tobacco is singularly responsible for most cases of cancer and coronary artery disease (CAD). Efforts to stop tobacco-use need to be guided by social circumstances. It is believed that family milieu may play a role in tobacco addiction. We studied the prevalence and pattern of tobacco-use in families of 50 consecutive tobacco-user patients who presented to a tobacco-cessation clinic and compared with age- and gendermatched controls (non-users of tobacco). The tobacco-use rates were significantly higher in the family of patients with tobacco-use compared to the control group. We conclude that problems of tobacco-use are not related to individual phenomenon, and efforts for control of tobacco addiction must be focused on entire family. J HEALTH POPUL NUTR 2013 Mar;31(1):130-132 DOI: http://dx.doi.org/10.3329/jhpn.v31i1.14757